Education that liberates and educates according to the perspective of the Qur’an - Ahmad Zain Sarnoto; Sri Tuti Rahmawati; Lamya Hayatina (Jurnal Konseling dan Pendidikan, 2021)
This study examines the concept of Islamic education with the paradigm of liberation and educating in the Quran. Islam which is based on the Quran has verses relating to education and the spirit of liberation. In addition to explaining universal principles, the Quran also presents historical figures as lessons. In general, Islamic education idealizes the birth of educational output that frees itself from the lusts that pollute the soul and frees its people from various kinds of social problems, such as injustice, economic inequality, discrimination and oppression. This type of research is library research. The approach used is an educational approach. His analytical theory uses hermeneutics and liberation education. The findings of this study: first, the verses of the Quran can be grouped into; verses of education and verses of liberation education. Second, Islamic education with a liberation paradigm must be in the form of practice, with a real social contribution; besides that it must also be based on the value of devotion and worship. This research contributes to the study of the interpretation of the Quran as well as the discipline of Islamic education, by presenting the category of verses of the Quran about education with a liberation paradigm.